Supply Behavior of Hydrous Ethanol in Brazil (Economia Aplicada, 2015)
This study built an economic model for hydrous ethanol and sugarcane supply. A panel data econometric model was used to estimate the economic models, using data from the main producer states in Brazil and for the period 2000/01—2012/13. The results indicated that the supply price elasticity for hydrous ethanol was 0.75 and that anhydrous ethanol price had a relevant influence on hydrous ethanol price through this period. For the sugarcane supply, the planted area and the number of newly installed plants were important determinants of the current planted area